Pengaruh Rasio Na₂SiO₃ : NaOH Terhadap Kuat Tekan Mortar Geopolimer Abu Sekam Padi - Abdi Nasrullah; Agil Puji Lestari (JURNAL ILMIAH BERING'S, 2022)
This research intent to analyse ash purpose influence rice husk ash and alkali solution compare activator to heavy duty geopolimer's mortar press, analysing purposes optimum proportion rice husk ash and activator alkali compare for geopolimer's mortar analyses if rice husk ash and activator alkali can be utilized for geopolimer's mortar. This research utilize experimental method which is examination at laboratory, with Ash composition mixture rice husk ash that utilizing to constitute rice husk ash that graduate No.200's filter, NaOH 's Solution concentration: Na₂SiO₃ are 16 m NaOH's heavy compares and Na₂SiO₃ are 2, 2. 25 and 2.5 Activator Alkali ratios to prekursor is 1:2 examination Age 3,7,14,21 and 28 days. This research is done at institut teknologi of Laboratory Pagar Alam. Examination is done at the age 3, 7, 14, and 28 days. To base result that is done, gotten by yan's pressing strength S1 the most high ratio 1:2 geopolimer's mortars ages 28 days as big as 13.06 Mpa.